Sastra Sasak Selayang Pandang - Dick van der Meij (Masyarakat Pernaskahan Nusantara, 2011)
This paper briefly explains Sasak literature on the island of Lombok. The description begins by explaining the importance of Islam for the Sasak people and the two variants of Islam practiced by them, namely Waktu Telu and Waktu Lima. Meanwhile, in the discussion of Sasak literature, it is explained that literature on Lombok Island has been passed down from generation to generation through writing on lontar palm leaves. The writing on these lontar leaves uses a type of Javanese script which in Lombok is called jejawen script, and the language used is Javanese. The Javanese language used in Sasak lontar carries the dialect of eastern coastal Javanese, but contains many vocabulary words unique to Sasak and is further mixed with words from Arabic, Malay, Balinese, and others, so that Lombok-style Javanese deserves to be considered a distinct Javanese dialect. At the end of this paper, several examples of stories known in Sasak literature are presented, namely the stories of Puspakrama, Bandarsela, Jowarsah, Cilinaya, and Kertanah. === Dalam tulisan ini dijelaskan secara ringkas mengenai kesusastraan Sasak di Pulau Lombok. Uraian diawali dengan menjelaskan pentingnya Agama Islam bagi orang Sasak dan dua varian agama Islam yang dianut oleh orang Sasak, yaitu Waktu Telu dan Waktu Lima. Sementara itu, dalam pembicaraan mengenai kesusastraan Sasak dijelaskan bahwa kesusastraan di Pulau Lombok diturunkan dari generasi ke generasi berikutnya lewat penulisan di daun lontar. Tulisan di daun lontar itu menggunakan sejenis aksara Jawa yang di Lombok disebut aksara jejawen dan bahasa yang digunakan adalah bahasa Jawa. Bahasa Jawa yang digunakan dalam lontar Sasak itu berbau logat Jawa pesisiran timur tetapi banyak kosa kata yang khas Sasak dan dicampur lagi dengan kata-kata dari bahasa Aran, Melayu, Bali dan lain sebagainya sehingga bahasa Jawa gaya Lombok selayaknya dianggap sebagai logat Jawa tersendiri. Di bagian akhir tulisan ini diberikan beberapa contoh cerita yang dikenal dalam kesusastraan Sasak, yaitu cerita Puspakrama, Bandarsela, Jowarsah, Cilinaya, dan Kertanah.